Characterization Studies on Waste Plastics as a Feedstock for Energy Recovery in Malaysia - Surenderan, L.; Saad, Juniza Md; Zhou, Hui; Neshaeimoghaddam, Hesam; Abdul Rahman, Adlansyah (International Journal of Engineering and Technology, 2018)
Increase in the energy usage and declining of non-renewable fossil fuels has changed the perceptions to energy recovery methods to satisfy the need of the energy. Through extensive research and innovation of technology, especially to recover the plastic waste to energy feedstock has been developed. The chosen plastic waste samples are polyethylene terephthalate (PET), high-density polyethylene (HDPE), and polypropylene (PP). This sample is collected from daily household waste and was characterized according to the resin types or plastic types. In this research the determination of the moisture content and ash analysis has been carried out using proximate analysis and also determination of the carbon, hydrogen, nitrogen, and sulphur content has been carried out by using the ultimate analysis. In addition, the calorific value of the samples has been determined and activation energy is obtained based on thermogravimetric analysis (TGA) data. The chosen kinetic modelling is modified Arrhenius equation. According to the results, HDPE was the best choice for energy recovery from waste plastics in Malaysia due to high calorific value, low activation energy, low moisture content and ash content and it has low sulphur content among all the plastic samples experimented.